Hydration of cement binders with mineral additives based on clay and carbonate rocks - V. V. Volodin; O. V. Tarakanov; T. A. Nizina; V. M. Kyashkin; A. S. Balykov (Vestnik MGSU)
Introduction. The use of mineral additives in cement concrete compositions makes it possible to reduce the consumption of Portland cement, which, with increasing construction rates, reduces the negative impact on the environment during its production. However, the high cost and territorial limitation of the production of the most effective modifiers (microsilica, metakaolin) do not allow to satisfy the growing demand for them. The development of mineral additives from widely used raw materials will help solve the problem of the deficit of the most common additives, as well as to reduce the consumption of Portland cement. The mechanism of hardening of Portland cement with widespread mineral additives was studied in sufficient detail. At the same time, there are practically no works describing the processes of hydration of cement binder modified with mineral additives based on thermally activated clay and carbonate rocks.Materials and methods. The following mineral additives were used: thermally activated clay (Nikitskoye deposit, Saransk, Republic of Mordovia), dolomite (Elniki village, Republic of Mordovia), thermally activated mixture of clay and limestone (Atemar village, Republic of Mordovia). Using the method of X-ray phase analysis, the mechanisms of action of these mineral additives on hydration processes are considered.Results. It was established that the use of these mineral additives makes it possible to increase the degree of hydration of Portland cement and change the phase composition of the cement stone in a targeted manner.Conclusions. The data obtained indicate the prospects and relevance of the direction for the development of concretes with modifying additives based on thermally activated polymineral clays and carbonate rocks, which makes it possible to expand the range of modified cement composites produced today due to more complete use of the local mineral resource base.